Manifestações caricaturais em jornais: estratégias do discurso visual na imprensa rio-grandina do século XIX - Sandri, Tammie Caruse Faria (2012)
This research seeks to analyze the graphical composition of manifestations of caricature in Rio Grande newspapers, from the issue on the strategies used in visual discourse to attract the reader's attention, guide the interpretation, provide information, and even promote the newspaper media. The theoretical and methodological framework is based on Image Theory, which discriminate the morphological, dynamic and scalar elements, that make up the manifestations of caricatures at newspapers Diabrete, Marui and Bisturi, to check the strategies for producing the images meaning and how the visual discourse contributes to the journalistic motives. Although the meanings of an image are not dissociated from its social and historical context of production or its verbal content, if it exists, the fundamental purpose of this dissertation is to understand and explain the power of visual language. This study seeks to demonstrate that, as the name used for this press time, the manifestations of caricatures, by guide the editorial strategy, represent a new genre of communication that shows a simple structure in its elements and, therefore, a strong appeal to reading and forming public opinion, being a resource for the production of information.